Peran Penyuluh Agama dalam Pembinaan Keagamaan Masyarakat: Strategi, Tantangan, dan Dampaknya di Dusun Gondang Pringkuku - Ikfan Taufiq; Dian Tias Aorta (ALSYS, 2026)
Although social change and the implementation of social affairs programs have received attention in various previous studies, studies that specifically examine community responses to the implementation of social programs in local rural contexts, particularly in Pringkuku Subdistrict, remain relatively limited. This study aimed to analyze the dynamics of community responses to the implementation of social affairs programs and to identify the factors that influence them. This study used a qualitative approach with a case study design, involving 20 informants selected through purposive sampling. Data were collected through in-depth interviews, field observations, and documentation, and were then analyzed using thematic analysis techniques. The results showed that community responses were divided into three main categories, namely positive, moderate, and critical responses, which were influenced by social experiences, the level of understanding of policies, and perceptions of program effectiveness. In addition, policy communication and the level of community participation were key elements in determining the success of social program implementation. These findings contribute to the development of studies on social change, particularly in understanding the relationship between public policy and community responses at the local level. The conclusion of this study emphasizes the importance of participatory approaches and effective communication in the implementation of social programs. The implications of this study indicate the need for local governments and policymakers to improve transparency, socialization, and active community involvement so that social programs become more adaptive and responsive to the needs of local communities, while also opening opportunities for further research on the effectiveness of social programs through quantitative or mixed-methods approaches with broader regional coverage.